2019
DOI: 10.1002/ejp.1495
|View full text |Cite
|
Sign up to set email alerts
|

High‐dose phenylephrine increases meningeal blood flow through TRPV1 receptor activation and release of calcitonin gene‐related peptide

Abstract: Background The α1‐adrenoceptor agonist, phenylephrine, is used at high concentrations as a mydriatic agent and for the treatment of nasal congestion. Among its adverse side‐effects transient burning sensations are reported indicating activation of the trigeminal nociceptive system. Methods Neuropeptide release, calcium imaging and meningeal blood flow recordings were applied in rodent models of meningeal nociception to clarify possible receptor mechanisms underlying these pain phenomena. Results Phenylephrine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 51 publications
0
10
0
Order By: Relevance
“…Alternatively, Dux et al. have recently reported that phenylephrine causes trigeminal nociception and increases meningeal blood flow through TRPV1 receptor activation and release of CGRP (83). Likewise, endothelin-1 on its own can induce pain-like behaviors in rodents (84) and can sensitize nociceptors and enhance release of glutamate in sensory neurons (85).…”
Section: Discussionmentioning
confidence: 99%
“…Alternatively, Dux et al. have recently reported that phenylephrine causes trigeminal nociception and increases meningeal blood flow through TRPV1 receptor activation and release of CGRP (83). Likewise, endothelin-1 on its own can induce pain-like behaviors in rodents (84) and can sensitize nociceptors and enhance release of glutamate in sensory neurons (85).…”
Section: Discussionmentioning
confidence: 99%
“…Results obtained in trigeminal neurons of TRPV1-deficient animals supported this observation. Phenylephrine-induced calcium transients and CGRP release were abolished in trigeminal ganglion neurons of TRPV1-deficient animals [36].…”
Section: Medication-induced Trigeminal Nociception and Painmentioning
confidence: 89%
“…Trigeminal ganglia in situ or cultivated trigeminal ganglion cells from rodents are frequently used to measure the release of substances following stimulation with noxious agents that target TRPV1 and TRPA1 receptors [35,36]. Particularly quantification of CGRP release from trigeminal ganglia or trigeminal cell cultures induced by capsaicin is regarded as a parameter for trigeminal activation and sensitization [37,38].…”
Section: Neuropeptide Releasementioning
confidence: 99%
See 2 more Smart Citations